In or outside the box? Citizen action between institutional and extra-institutional channels in Chinese environmental governance - Guo, Danqi; Bondes, Maria; Kostka, Genia; Rabe, Wiebke (Journal of Environmental Policy & Planning, 2024)
Authoritarian leaders around the world have recognized that citizen engagement is a core element of successful environmental governance. Faced with a massive environmental crisis, also authoritarian China is mobilizing its citizens to address its ecological problems. However, taking a functional approach to public participation, the Chinese party-state like other authoritarian regimes attempts to channel citizen action into institutional pathways and away from more contentious extra-institutional ones. Little research has investigated citizens’ reactions to such attempts. This paper analyses citizen participation between institutional and extra-institutional venues at the case of Chinese environmental governance. It finds that Chinese citizens use a mix of both channel types, but are overall more drawn to extra-institutional channels despite the risks. Moreover, our findings point to different motivations for the use of venues: personal grievances are more linked with the use of institutional channels, broader environmental concerns with extra-institutional ones. This shows, first, that channeling attempts have not yet been successful in crowding out noninstitutional channels. And second, that citizens seem to attach different meanings to the different channel types. This will make it hard for the Chinese and other authoritarian regimes to phase out extra-institutional action without severe losses for the effectiveness of environmental governance.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Environmental participation; environmentalism; institutional channels; motivation; noninstitutional channels; preference

Public Participation in China's State-Created ICT Spaces: Explaining Participation Patterns - Rabe, Wiebke; Bondes, Maria; Abels, Christoph M.; Kostka, Genia (Regulation & Governance, 2025)
It has become commonplace for non-democratic regimes to integrate information and communication technologies (ICTs) into their governance system. However, how citizens make use of these new digital opportunities in an authoritarian setting remains understudied. Based on an online survey in China in 2021, we find that a surprisingly large share of Chinese citizens engages with the new ICT-based participatory venues. But ICTs seem to unfold their potential only for certain groups such as tech-savvy younger citizens with a higher income. Moreover, while citizens seem to be quite aware of the risks of using ICTs, such as data security breaches or digital surveillance, these do not seem to hamper participation. Rather, citizens trade off perceived risks for perceived benefits, such as higher levels of convenience, efficiency, or expected government responsiveness. Our study contributes to the literature on digital governance in authoritarian regimes, and the digital divide and technology acceptance literatures. Moreover, amid the tightening of political control in China, it offers insights into participatory developments under Xi Jinping.
CRIS-Team Scopus Importer:2025-11-07
Keywords: China; digital divide; digital governance; public participation; state–society relations